LabVIEW-Based Analysis of EEG Signals in Determination of Sleep Stages - Guzel, Seda; Kaya, Turgay; Guler, Hasan (Ieee, 2015)
The aim of this study is to create an interface for classification of sleep stages. Classification was made by examining of Electroencephalogram (EEG) that plays an important role in understanding and treatment of various diseases. The user interface was generated by means of Laboratory Virtual Instrument Engineering Workbench (LabVIEW) that has visual programming language. EEG signals in the time, frequency and time-frequency domain were analyzed by generated interface. Also EEG signals were studied by using MATLAB as well as LabVIEW. The control of interface was made by using signals that received from Firat University Hospital, signals which found in software and the generated signals by LabVIEW EEG simulator.
Uyku Evrelerinin Belirlenmesinde EEG Sinyallerinin LabVIEW Tabanli Analizi
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: EEG; LabVIEW; PSD; Sleep Stages